Effects of salidroside on atherosclerosis: potential contribution of gut microbiota - Si-Fan Fei; Can Hou; Fang Jia (Frontiers Media S.A., 2024)
Much research describes gut microbiota in atherosclerotic cardiovascular diseases (ASCVD) for that the composition of the intestinal microbiome or its metabolites can directly participate in the development of endothelial dysfunction, atherosclerosis and its adverse complications. Salidroside, a natural phenylpropane glycoside, exhibits promising biological activity against the progression of ASCVD. Recent studies suggested that the gut microbiota played a crucial role in mediating the diverse beneficial effects of salidroside on health. Here, we describe the protective effects of salidroside against the progression of atherosclerosis. Salidroside regulates the abundance of gut microbiotas and gut microbe-dependent metabolites. Moreover, salidroside improves intestinal barrier function and maintains intestinal epithelial barrier function integrity. In addition, salidroside attenuates the inflammatory responses exacerbated by gut microbiota disturbance. This review delves into how salidroside functions to ameliorate atherosclerosis by focusing on its interaction with gut microbiota, uncovering the potential roles of gut microbiota in the diverse biological impacts of salidroside.